2023
DOI: 10.1093/hmg/ddad117
|View full text |Cite
|
Sign up to set email alerts
|

COL11A2 as a candidate gene for vertebral malformations and congenital scoliosis

Denise Rebello,
Elizabeth Wohler,
Vida Erfani
et al.

Abstract: Human vertebral malformations (VMs) have an estimated incidence of 1/2000 and are associated with significant health problems including congenital scoliosis (CS) and recurrent organ system malformation syndromes such as VACTERL. The genetic cause for the vast majority of VMs are unknown. In a CS/VM patient cohort, three COL11A2 variants (R130W, R1407L, R1413H) were identified in two patients with cervical VM. A third patient with a T9 hemivertebra and the R130W variant was identified from a separate study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…NC was enriched for matrisome proteins already described in the IVD context in human or other animal models such as COL2A1 , COL11A2 , ACAN , HAPLN3 , PRELP , SPP1 , FN1 , SLIT2 , SHH , BMP3 , LGALS3 , SEMA3C , CD109 , TIMP3 . 25 , 56 , 61 , 63 , 66 , 67 , 68 , 69 , 72 , 90 , 91 , 92 , 93 , 94 Interestingly, the analysis highlighted SEMA3C , SULF2 , HSPG2 and P4HA1 proteins, not yet described in this developmental context. They have been involved in mediating Hedgehog signaling or in post-translational ECM proteins modifications.…”
Section: Resultsmentioning
confidence: 84%
“…NC was enriched for matrisome proteins already described in the IVD context in human or other animal models such as COL2A1 , COL11A2 , ACAN , HAPLN3 , PRELP , SPP1 , FN1 , SLIT2 , SHH , BMP3 , LGALS3 , SEMA3C , CD109 , TIMP3 . 25 , 56 , 61 , 63 , 66 , 67 , 68 , 69 , 72 , 90 , 91 , 92 , 93 , 94 Interestingly, the analysis highlighted SEMA3C , SULF2 , HSPG2 and P4HA1 proteins, not yet described in this developmental context. They have been involved in mediating Hedgehog signaling or in post-translational ECM proteins modifications.…”
Section: Resultsmentioning
confidence: 84%
“…Notably, common COL11A1 variants also have been associated with adult lumbar disc herniation and lumbar disc degeneration, as well as DXA-measured bone size, spinal stenosis, and spondylolisthesis ( Jiang et al, 2017 ; Mio et al, 2007 ; Styrkarsdottir et al, 2019 ). Although gain-of-function or dominant-negative effects of the rs3753841 variant would not have been revealed in our assays, the spinal deformity noted in the cho / cho loss-of-function model, and failure of missense variants in Col11a2 to rescue congenital scoliosis ( Rebello et al, 2023 ), leads us to surmise that reduction in the components of collagen type XI disrupts spinal development.…”
Section: Discussionmentioning
confidence: 82%
“…In zebrafish, several genetic mutants with larval or later-onset spinal deformity have been described, including ptk7 ( Hayes et al, 2014 ; Van Gennip et al, 2018 ), c21orf59 ( Jaffe et al, 2016 ), ccdc40 ( Becker-Heck et al, 2011 ), ccdc151 ( Bachmann-Gagescu et al, 2011 ), dyx1c1 , and kif6 ( Konjikusic et al, 2018 ). In rescue experiments, Rebello et al recently showed that missense variants in COL11A2 associated with human congenital scoliosis fail to rescue a vertebral malformation phenotype in a zebrafish col11a2 knockout line ( Rebello et al, 2023 ). In mouse, conditional deletion of Adgrg6 in skeletal cartilage (using Col2a1 -Cre) produces a progressive scoliosis of the thoracic spine during postnatal development that is marked by herniations within the cartilaginous endplates of involved vertebrae.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach to modeling is to simulate the symptoms of the target disease through mutations in genes with known function. Individuals and lines have been created that exhibit analogs of human somatic diseases such as cataract [ 49 , 50 ], myopia [ 51 ], exfoliative syndrome [ 52 ], retinal dysfunction [ 53 , 54 ], congenital heart defect [ 55 ], cardiac hypertrophy [ 56 ], dilated cardiomyopathy [ 57 ], arrhythmia [ 58 ], autoinflammatory syndrome [ 59 ], metabolic syndrome [ 60 ], diabetes and obesity [ 61 ], tuberculosis [ 62 ], thrombocytopenia [ 63 ], pediatric intestinal pseudoobstruction [ 64 ], pediatric cirrhosis [ 65 ], congenital hypothyroidism [ 66 ], fatty or alcoholic hepatosis [ 67 ], and scoliosis [ 68 , 69 ]. Genome editing has been used to model human tumors such as liver cancer [ 70 ], paraganglioma [ 71 ], skin melanoma [ 72 ], and epithelioid sarcoma [ 73 ].…”
Section: Genome Editing In Salmonidae and Cyprinidae Aquaculture Fish...mentioning
confidence: 99%